The Play-Based Behaviours of Emirati Preschool Children: A descriptive cultural study of children’s play habits and review of current play-based practices in Dubai - Al-Qinneh, Dana (2019)
The United Arab Emirates current policy and curriculum guide for Early Childhood Education Centers advocates for the use of play-based approaches and emphasizes the importance of child-centered learning practices, similar to those advocated for in the West. However, effective pedagogical approaches for best practice reforms must reflect a sociocultural perspective and suit the context of application. The main targets of the research were to first, uncover the way in which Emirati children’s and Western children’s’ play is scaffolded. Second, to outline the routines, habits, play partners and play themes that dominate an Emirati child’s play. Third, to explore the social, cultural and maternal values which contribute to influencing the play behaviors of Emirati children, and lastly, to suggest policies that better support Emirati children based on play-based behaviors discovered. The findings of this descriptive study aim to shed light on the cultural aspects of the play behaviors of upper middle-class children in the United Arab Emirates in contrast to European middle-class children living in the U.A.E to describe any difference from a sociocultural perspective and cultural context affecting their play-behaviors. The central aim is in primarily drawing the attention of policy makers and educators to the issue of cultural and contextual appropriateness in applying Western pedagogies in teaching preschool children of Emirati background in the U.A.E. Through questionnaires with the mothers of 34 preschool children (29 Emirati and 5 European children) the children’s daily activities, routines, family values, cultural aspects and play behaviors were investigated. The influences which play a role in shaping a child’s behavior were examined in the form of investigating children’s play partners, home activities and free time allocated to play. Qualitative and quantitative questionnaires were used in order to assess a wider range of answers on things such as time set aside by parents to play with their children, time spent playing with housekeepers or nannies, time spent watching tv, frequency of outings with child, amount of time spent indoors versus outdoors, amount of toys available to the children, typical themes children engaged in while playing and amount of time spent with child in general after nursery hours of both Emirati and European maternal views. The majority of the play partners of Emirati children were nannies and relatives, while many mothers wished it was them instead. Emirati mothers were well aware of the significance of play, however were less aware of “child-led” play practices and habits, and thus were significantly less likely to facilitate child-led play times when compared to Western mothers. Despite a belief in the significance of play, Emirati mothers preferred a compromise between a play-based learning environment and a formal education environment for their preschool children.